2010
DOI: 10.1073/pnas.0910809107
|View full text |Cite
|
Sign up to set email alerts
|

Simulated atmospheric processing of iron oxyhydroxide minerals at low pH: Roles of particle size and acid anion in iron dissolution

Abstract: A number of recent studies have shown that iron dissolution in Fe-containing dust aerosol can be linked to source material (mineral or anthropogenic), mineralogy, and iron speciation. All of these factors need to be incorporated into atmospheric chemistry models if these models are to accurately predict the impact of Fe-containing dusts into open ocean waters. In this report, we combine dissolution measurements along with spectroscopy and microscopy to focus on nanoscale size effects in the dissolution of Fe-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(157 citation statements)
references
References 38 publications
4
149
3
1
Order By: Relevance
“…However, this Fe pool exhibited a reactivity between that of the "fast" and "slow" pools. We speculate here that the "intermediate" pool was mainly composed of nano-sized Fe oxides, which have been found in natural soil dust samples (Shi et al, 2011) and which are known to have a reactivity between highly crystalline/larger size Fe oxides and poorly crystalline Fe oxides (Rubasinghege et al, 2010;Schwertmann, 1991).…”
Section: Link Between Fe Mineralogy and The Three Fe Poolsmentioning
confidence: 80%
“…However, this Fe pool exhibited a reactivity between that of the "fast" and "slow" pools. We speculate here that the "intermediate" pool was mainly composed of nano-sized Fe oxides, which have been found in natural soil dust samples (Shi et al, 2011) and which are known to have a reactivity between highly crystalline/larger size Fe oxides and poorly crystalline Fe oxides (Rubasinghege et al, 2010;Schwertmann, 1991).…”
Section: Link Between Fe Mineralogy and The Three Fe Poolsmentioning
confidence: 80%
“…The emitted FeOOH aerosol plumes convert into the ISA plume immediately after leaving the emission sources due to the high reactivity of flame pyrolytic Fe oxides. The time it takes to cover the flame-pyrolytic FeOOH particle surface with Fe(III) chlorides through HCl absorption from the gaseous phase is several times shorter that than necessary for the generation of iron chlorides from natural iron oxide minerals in loess dust particles (Rubasinghege et al, 2010;Sullivan et al, 2007).…”
Section: The Isa Method: How To Increase Artificial Iron Emissionsmentioning
confidence: 99%
“…For example, Ghio et al (1999) reported that soluble iron concentrations correlate with sulfate concentrations in particle filters and that the ability of soluble extracts from the particles to generate damaging oxidants is directly proportional to the sulfate concentrations. More recently, Rubasinghege et al (2010) simulated the transformation of non-bioavailable iron to dissolved and (hence) bioavailable iron in atmospheric iron particles in the presence of acids, in both light and dark conditions. The presence of sulfuric acid on the particles results in a dramatic increase in the bioavailable iron.…”
Section: Inorganic Aerosols and Metalsmentioning
confidence: 99%